Evaluating the Development Level of Digital Economies Using the Topsis Comprehensive Assessment Approach: – A Case Study of China’s Provincial Regions - Liu, Yanlin (Transactions on Economics, Business and Management Research, 2024)
The digital economy, as a pivotal engine of global economic advancement, reached a valuation of 50.2 trillion yuan in China in 2022, making up 41.5% of the GDP. This research established an evaluative framework for digital economy progress featuring 1 primary indicator, 4 secondary indicators, and 17 tertiary indicators. Weights were assigned using the Analytic Hierarchy Process, and the development of the digital economy across China’s 31 provincial regions in 2022 was assessed through the Topsis comprehensive assessment method. The findings indicate that Guangdong is at the forefront of digital economy development, whereas Qinghai remains relatively underdeveloped. Drawing on these observations, the paper proposes targeted policy measures aimed at encouraging equitable growth of the digital economy and inclusive regional economic development.